(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article studies the financial analysis of the directions of financing the population in need of social protection through the social insurance system. The results of economic and statistical analyses of each type of social insurance, the application of pensions and benefits, and the targeted and targeted delivery of software for their payment are studied. The growth in the number of social benefit recipients in our country and the amount of material assistance provided to low-income families, as well as their financial sources are cited. The implementation of the social insurance system necessarily requires a certain level of financial resources. Therefore, social funds are an integral part of any economic mechanism. As is known, in order to protect the most vulnerable segments of the population, there is a need for a certain redistribution of income.